KANDUNGAN NUTRIEN RUMPUT Brachiaria brizantha cv. MG 5 DENGAN MATERIAL TANAM BERBEDA PADA REGROWTH KE-1: QUALITY NUTRIENT OF Brachiaria brizantha cv. MG 5 WITH THE DIFFERENT PLANT MATERIAL ON REGROWTH 1st - Zaini, Nur (Tropical Animal Science, 2023)
This research was aimed to know the quality of brachiaria brizantha cv. MG 5 grass including the nutrien content, which contains the quality of dry, organic matter and crude fiber planted with different material plant on regrowth 1. The treatment material plant were pols (vegetatif) and seed (generatif) of Brachiaria brizantha cv. MG 5. Planted with 1 seed, 2 seeds, 1 pols and 2 pols per/hole. The plant was cut at the 45th day after regrowth-1. The harvested Brachiaria brizantha cv. MG 5 grass put in an oven with 55oC temperature and grinded resulting samples going to analyzed with proximate. The obtained data were analyzed bay using split plot design and continued with Duncan’s Multiple Range Test (DMRT). The result showed use different plant material of Brachiaria brizantha cv. MG 5 that affected (P<0,05) to dry matter. But different plant material that not affected (P>0,05) to organic matter, crude fiber. The average of dry matter 1 seed (16,33%), 2 seeds (21,66%), 1 pols (12,66%) and 2 pols (16%). The conclusion of research result concludes that plant material two seeds per hole shown the best result for the quality nutrien